A54: Insulin Sensitivity Is Improved in sJIA Children With Insulin Resistance After Tocilizumab Treatment: Results From the TENDER Study. Issue Volume 66:Issue(2014)supplement 3 (March 2014) - Mirjafari, Hoda; Ruperto, Nicolino; Brunner, Hermine I.; Zuber, Zbigniew; Zulian, Francesco; Maldonado‐Velázquez, Maria del Rocio; Mantzourani, Evangelia; Murray, Kevin; Roth, Johannes; Rovensky, Jozef; Vougiouka, Olga; Wang, Jianmei; et al.
Abstract : Background/Purpose: In adults with inflammatory arthritis, insulin resistance (IR) is associated with diabetes and cardiovascular disease. Interleukin‐6 (IL‐6) is postulated to play a mechanistic role in IR. The aim of this study was to evaluate the degree of IR among children with systemic juvenile idiopathic arthritis (sJIA) and to determine whether treatment with tocilizumab (TCZ) results in attenuation of IR in sJIA. Methods: Patients from TENDER1 were included if baseline and week 6 fasting insulin were measured. Glucocorticoid tapering was not permitted until week 6. Insulin sensitivity was quantified using the homeostatic model of insulin resistance (HOMA‐IR). Patients were classified as having IR if their HOMA‐IR was ≥2.2 U. Change in HOMA‐IR after 6 weeks was assessed using paired t‐test. Baseline associations with HOMA‐IR and factors predicting change of HOMA‐IR from baseline were assessed using regression analyses. Factors changing in association with HOMA‐IR change were assessed. Results: Ninety‐two patients with sJIA were analyzed. 62 were randomly assigned to TCZ and 30 to placebo, 12 of whom required escape therapy with TCZ by week 6. At baseline, 40 patients (43%) had IR. Baseline HOMA‐IR was associated with higher standardized body mass index and higher IL‐6 levels (β‐coefficients [95% CI]: 0.20 [0.05, 0.35] and 0.019 [0.001, 0.038], respectively) but not with JADAS, CRP, active joint count, or presence of fever. Of the 74 patients who received TCZ, 34 (46%) had IR at baseline, including 4 patients who escaped from the placebo arm, compared with 6/18 (33%) who received only placebo. IR patients treated with TCZ but not placebo had significant reductions in HOMA‐IR at week 6 (1 ). Across all IR patients, improvement in JADAS and active joint count was not associated with improvement in HOMA‐IR (β‐coefficients [95% CI]: 0.04 [−0.07, 0.14] and 0.08 [−0.06, 0.22], respectively). Conclusion: After only 6 weeks of TCZ treatment, HOMA‐IR was improved in IR patients with sJIA in the presence of unchanged glucocorticoid dose. These data support a mechanistic contribution of IL‐6 to IR in vivo in humans.